(3NWhGJ ejSQI JYJeO GdeTGQcI GdCgdjI cCSdhH aj JNWjW GdeTQhYGJ eY GdJQcjR Ydi eTQhYGJ GdJfejI GdGLJeGYjI ZjQ GdQHMjIs - (3MSjf eMeO(B, (3MSfjfs ((3YeGf(B:s (3OGQ eLOdGhj(B,s, 2002)
(3eQGMd JNWjW GdeTQhY(B- (3JMOjO acQI GdeTQhY(B- (3LeY GdeYdheGJ(B- (3UjGZI CgOGa GdeTQhY(B-(3JhKjb GdeTQhY(B- (3Jehjd GdeTQhY(B- (3JfajP GdeTQhY(B- (3Jbhje GdeTQhYs
Keywords: (3GdJNWjWs; (3GdJbhjes; (3GdeTQhYGJs